Las actividades complementarias de las explotaciones agrícolas peruanas - Pascale Phélinas (Bulletin de l'Institut Français d'Études Andines, 2002)
Diversifying sources of farming income is a crucial issue for the welfare of rural populations. Indeed, in rural areas, any additional work dedicated to activities that are not directly related to farming may contribute to rises in income, albeit modest. This paper demonstrates that, despite the potential of activities that complement farming, both in terms of job creation and income generation, there continues to be little understanding of this area of rural economy. This weakness is due to the heterogeneity of such activities, which produces a great deal of conceptual confusion, and to the shortcomings of national statistics, which do not register these activities properly. In spite of these difficulties, this paper seeks to provide an overview of the importance and characteristics of the activities that complement farming in Peru. Four main conclusions emerge from the results presented here: the unquestionable underestimation of these activities and the income they generate; the significant proportion of agriculture in complementary activities; the concentration of these activities in two or three sectors and the relative stability of their distribution in time and space, according to sectors; and a rather marked division of labor between men and women.